Ellis Island - Bourgoujian, Lisa; Haffner, Craig; Lusitana, Donna E.; Patinkin, Mandy; History Channel (Television network); Greystone Communications; A & E Home Video (Firm); New Video Group ([New York] : New Video Group, 1997)
Immigrants of diverse ethnic backgrounds recall their extraordinary adventures, historians explore the sometimes insensitive national policies, and the Ellis Island Oral History Project reveals what the immigration experience was actually like. Features rare photographs and film.
Special features: interactive timeline of key Ellis Island historical events, interactive menus and scene selection.
Director of photography, B.C. Callahan; editor, Stephen Pomerantz; music, Christopher L. Stone, Zeljko Marasovich.
Host/narrator: Mandy Patinkin.
DVD.
Keywords: Ellis Island Immigration Station (N.Y. and N.J.) -- History; Immigrants -- United States -- Biography; United States -- Emigration and immigration -- History; Video (DVD); Documentary television programs